BIOREMEDIASI Cd DAN KETERSEDIAAN P BATUAN FOSFAT OLEH CENDAWAN EKTOMIKORHIZA (Pisolithus tinctorius dan Suillus granulatus) DALAM KULTUR MURNI - Tini Surtiningsih (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1997)
Some rock phosphates used as fertilizers or to produce fertilizers which containing very high cadmium and have been suspected to increase trace element content in soild. In order to know if the cadmium can be mobilized, we have studied the bio-remediation of Cd and bio-availibility of P from three rock phosphates (from North Caroline, Togo and Senegal) by ectomycorrhyzal fungi (Pisolithus tinctorius and Suillus granulatus) in pure culture. In pure culture the fungi accumulated 80-100% Cd soluble. In the experiments, the % bio-accumulation or bio-remediation of Cd was not always correlated with the Cd content of the phosphate nor their hardness.